Role of creativity in enhancing visitors' experience in outdoor recreation activities: a preliminary study - Isa, Siti Suriawati; Aziz, Azlizam (Forestry Department Peninsular Malaysia, 2013)
Creativity and innovation are becoming key elements to attract visitors to a destination in this era. These elements will provide a better understanding of the activities that the market player and stakeholders' have to offer that can satisfy the needs and wants from the market. Based on that notion this study was undertaken to examine creativity and innovation elements used by Malaysian outdoor recreation stakeholders and market players for their activities at selected popular tourism destinations. Mixed methods were applied to get an in depth understanding about this topic. Personal interviews with the stakeholders, market players and outdoor recreation users were conducted in the first stage. The results of the initial phase of the study indicate that the outdoor recreation development in Kedah is limited, in Pahang there are areas for improvement while in Selangor, development needs more creative approaches. This study found that outdoor recreation has substantial potential in Kedah, Pahang and Selangor due to their rich natural resources suitable for outdoor recreation activities. However, creativity is still lacking relating to the activities and marketing aspects in outdoor recreation.